ANALISIS BUDAYA KERJA ORGANISASI PADA BIDANG PAIS KANWIL KEMENTERIAN AGAMA PROVINSI JAWA TIMUR - Andyni Loisalina Hidayat; Shabrina yudhitia Alfiatun nafiah; Moh qoidul Ghurril muhajjilin; Azis Daryaji (STKIP Subang, 2026)
This study aims to analyze the organizational work culture in the Islamic Education Division (PAIS) of the Regional Office of the Ministry of Religious Affairs of East Java Province. The research used a qualitative approach with a descriptive type of research. Data were collected through observation, interviews, and documentation involving the head of division, employees, and staff of PAIS. The results of the study indicate that the implementation of organizational work culture in the PAIS Division has been carried out quite well through the application of the five work culture values of the Ministry of Religious Affairs, namely integrity, professionalism, innovation, responsibility, and exemplary behavior. These values are reflected in employee discipline, work professionalism, utilization of technology, and responsibility in carrying out educational service programs. The study also found several strengths, such as good cooperation among employees, leadership support, and the use of digital technology in organizational activities. However, there are also several weaknesses and challenges, including differences in employee discipline, adaptation to technological developments, and increasing administrative workloads. Overall, the organizational work culture in the PAIS Division contributes positively to improving employee performance and the quality of public services in the field of Islamic education.